Practice patterns to decrease myopia progression differ among paediatric ophthalmologists around the world. Issue 4 (13th August 2019) - Leshno, Ari; Farzavandi, Sonal K; Gomez-de-Liaño, Rosario; Sprunger, Derek T; Wygnanski-Jaffe, Tamara; Mezer, Eedy
Abstract : Introduction: Myopia is a worldwide epidemic. Plethora of treatments are offered to decrease myopia progression. In this study, we compared between different geographical areas worldwide the practice patterns used by paediatric ophthalmologists to decrease the progression of myopia. Methods: Global responses to a questionnaire were analysed (n=794) for demographic variations. Pharmacological, optical and behavioural categories were defined as effective or ineffective based on the current scientific peer reviewed literature. Results: Treatment rates varied significantly between geographical regions (mean 57%, range 39%–89%, p<0.001). Nearly all participants who treat myopia used at least one form of effective treatment, regardless of location (98%, p=0.16). Among those prescribing pharmacological treatments, European physicians offered the lowest rate of effective treatment compared with other regions (85% vs mean 97%). Rates of effective optical treatment varied significantly between locations (p<0.001), from 16% (Central-South America) to 56% (Far East). Most treating respondents advocated behavioural modifications (92%), between 87% (North America) and 100% (Central Asia). Nearly all respondents used combinations of treatment modalities (95%)—mostly pharmacological, optical and behavioural combination. However, combination rates varied significantly between regions (p<0.001). Discussion: The utility of treatment to decrease myopia progression differs significantly across the world both in type, combination and efficacy. Conclusion: Paediatric ophthalmologists involvement and proficiency in myopia progression treatment varies around the world. This may entail promoting continuous medical education and other incentives to increase the number and proficiency of paediatric ophthalmologist to have a more effective impact to control the myopia epidemic in children.